Ondel-Ondel: Looking for a Theoretical Explanation - Yuwastina, Desti; Volodymyr, Kyrychenko (Paradigma: Jurnal Kajian Budaya, 2021)
Ondel-ondel, initially believed to have fearsome characteristics and magical ability to ward evil spirits off, is still performed in various areas in Jakarta on particular occasions. Ondel- ondel was originally an ancient artwork named barongan. This research aims to seek a theoretical explanation of the ondel-ondel phenomenon by examining the relationship between the media and local culture. Several defining features of postmodernism are incorporated to reframe ondel-ondel as a form of entertainment, along with the interplay between the tradition and technology-assisted media. This paper seeks to reveal the actual meaning of ondel-ondel for locals and non-locals during their encounters with ondel-ondel. The research found (1) that ondel-ondel is an attempt to reinvent the way people seek entertainment in the face of changes brought about by modernity and (2) that the presence of ondel-ondel communicated in the virtual space generates digital traces in the form of messages contributing to the creation and the re-creation of ondel- ondel itself.